Small cell neuroendocrine carcinoma: A rare second primary malignancy after treatment of nasopharyngeal carcinoma - Krishnamoorthy Madhusudhan; Nor Eyzawiah binti Hassan; Norasnieda Binti Md Shukri; Shahrul Bin Hitam; Ikmal Hisyam Bin Bakrin (Sciendo, 2024)
Non-Indexed Publication